Cold start investigation of fuel cell vehicles with coolant preheating strategy. (25th January 2022) - Luo, Mengzhu; Zhang, Jun; Zhang, Caizhi; Chin, Cheng Siong; Ran, Hongxu; Fan, Min; Du, Kun; Shuai, Qi
Highlights: Cold start of fuel cell vehicles with an integrated coolant preheating system. Verify the feasibility of the coolant preheating strategy for fuel cell vehicles. Utilize the heat generated by the fuel cell to reduce the cold start time. The lowest cell voltage appearing at ends of the stack affects cold start process. Abstract: Fast cold startup of fuel cell vehicles is critical to its commercialization. Normally, fuel cell vehicles integrate a preheating system based on coolant to achieve fast cold startup. In this work, the cold start experiments of a fuel cell vehicle at −20 °C and −30 °C were conducted to analyze the feasibility of the system design and the effectiveness of the cold start strategy. The novelty of this work is to study the output characteristics, voltage consistency, heat generation and heat dissipation changes of the fuel cell system through system-level experiments. The experimental results show that the cold start strategy of coolant preheating can achieve a successful start at −30 °C. Still, the preheating time is relatively long, and the total cold start time can be shortened by well utilizing the heat generated by the fuel cell. Meanwhile, when the temperature is in the vicinity of 0 °C, the output power of the fuel cell is prone to fluctuate and the voltage uniformity deteriorates. Moreover, the higher the output power of the fuel cell, the worse the voltage uniformity, due to the uneven distribution of reactant gas, generated water and heat in the stack at high output power. This paper provides a deeply experimental analysis of the cold start strategy of coolant preheating at a system level, which can provide direction for optimizing the cold start strategy of fuel cell vehicles.